Baryon stopping probes geometric scaling - Mehtar-Tani, Yacine; Wolschin, Georg (Nuclear physics. A, Nuclear and hadronic physics, 2010)
We investigate baryon transport in relativistic heavy-ion collisions at energies reached at SPS, RHIC and LHC in the model of saturation. An analytical scaling law is derived within the color glass condensate framework based on small-coupling QCD. Transverse momentum spectra, net-baryon rapidity distributions and their energy, mass and centrality dependences are well described. In a comparison with RHIC data in Au + Au collisions at sNN=62.4GeV and 200 GeV, the gradual approach to the gluon saturation regime is investigated, and limits for the saturation-scale exponent are determined. Predictions for net-baryon rapidity spectra and the mean rapidity loss in central Pb + Pb collisions at LHC energies of sNN=5.52TeV are made.